RUTILE/TIO2II PHASE EQUILIBRIA - Withers A.C.; Essene E.J.; Zhang Y. (My University, 2003)
The transition between rutile and α-PbO2 structured TiO2 (TiO2II) has been investigated at 700-1,200 °C and 4.2-9.6 GPa. Hydrothermal phase equilibrium experiments were performed in the multi-anvil apparatus to bracket the phase boundary at 700, 1,000, and 1,200 °C. The equilibrium phase boundary is described by the equation: P (GPa)=1.29+0.0065 T ( °C). In addition, growth of TiO2II was observed in experiments at 500 and 600 °C, although growth of rutile was too slow to bracket unambiguously the equilibrium boundary at these temperatures. Water was not detected in either rutile or TiO2II, and dry synthesis experiments at 1,200 °C were consistent with the phase boundary determined in the fluid-bearing experiments, suggesting that the equilibrium is unaffected by the presence of water. Our bracket of the phase boundary at 700 °C is consistent with the reversed, dry experiments of Akaogi et al. (1992) and the reversals of Olsen et al. (1999). The new data suggest that the phase boundary is linear, in agreement with Akaogi et al. (1992), but in striking contrast to the phase diagram inferred by Olsen et al. (1999). The natural occurrence of TiO2II requires formation pressures considerably higher than the graphite-diamond phase boundary.
Keywords: rutile